Implementation of PID Control Algorithms and Fuzzy Logic based on robotics teaching with arduino applied to students: Implementation of PID Control Algorithms and Fuzzy Logic based on robotics teaching with arduino applied to students - CASTAÑEDA BARBARAN, MILAGROS DEL CARMEN (CLEI electronic journal, 2025)
This research paper addresses the implementation of robotic control algorithms applied to the educational environment, with the objective of improving the teaching of robotics to students. Educational mobile robots often use basic control systems, which limits their functionality and can present difficulties in task execution. The evaluation of more advanced robotic control algorithms, such as PID and fuzzy logic, in educational contexts, shows that they can significantly contribute to better performance and understanding in the teaching of educational robotics.